2019
DOI: 10.1111/mec.14998
|View full text |Cite
|
Sign up to set email alerts
|

Convergence, constraint and the potential for mutualism between ants and gut microbes

Abstract: Ants are a hugely diverse family of eusocial insects that dominate terrestrial ecosystems all over the planet. Did mutualistic gut microbes help ants to achieve their diversity and ecological dominance? Initial studies suggested the potential for widespread convergence in ant gut bacterial communities based on dietary niche, but it now seems possible that dedicated bacterial symbionts are restricted to a minority of ant lineages (Russell et al., 2017). Nevertheless, as most ants are omnivores, the evidence so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It was understandable for our herbivorous ants feed on plants (seeds), which contain large amounts of starch. This showed that there is a positive correlation between dietary specialization and the abundance of nutrient-providing bacteria in the ant gut [25]. Similarly, there were signi cant differences in the abundance of dominant gut bacteria among ants with different phylogenies (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…It was understandable for our herbivorous ants feed on plants (seeds), which contain large amounts of starch. This showed that there is a positive correlation between dietary specialization and the abundance of nutrient-providing bacteria in the ant gut [25]. Similarly, there were signi cant differences in the abundance of dominant gut bacteria among ants with different phylogenies (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…From the two ternary phase diagrams (Fig. S6), we found herbivorous ants, carnivorous ants, and omnivorous ants developed unique gut bacterial communities [25,42]. In the same way, Ponerinae ants, Formicinae ants, and Myrmicinae ants developed unique gut bacterial communities although the relative abundance of "speci c bacteria" was low.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The last decade has seen a great increase in the number of studies on microbial communities associated with ants Pringle, 2019). The 'omics' revolution allowed myrmecologists to deepen their view of ants' eco-evolutionary relationship with plants, herbivores, and fungi.…”
Section: Introductionmentioning
confidence: 99%